ANATOMY OF A SEMIARID COASTAL SYSTEM: THE UPPER CARNIAN OF LOMBARDY (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The mixed terrigenous-carbonate-evaporitic  S.Giovanni Bianco  Formation  and dolomitic Campolungo  Tongue  (upper part of the Breno Formation),  generally 2OO  to  3OO  m thick, are assigned  to the Late Carnian.  They  respectively  overlie lagoonal limestones  (Gorno  Fm.)  and peritidal  carbonates  (Annunciata Member of the Breno Fm.), and underlie  intraformational  breccias  and recrystallized  limestones  (Castro Fm.). Recognition of an unconformity,  ascribed  to a relative  fall of sea-level (sequence  boundary), allowed  us to subdivide the Upper  Carnian  succession  into two parts. ln the lower part (SGBL),  six lithosomes  were recognized. Red  to green  alluvial  clastics in the south-east  and south-west  pass northward  to mixed terrigenous-carbonate  coastal sediments  and finally to dolostones  deposited  in carbonate tidal flats. In the proximal sections  of the Brescia  Prealps,  renewed  north-westward  progradation  of alluvial redbeds  with  intercalated  calclithite conglomerates  points to a stage of teconic uplift. A distinct  increase  in quartz, representing a regional  petrographic  marker  followed  all  across Lombardy, indicates  deepening  of erosion  into the metamorphic wallrocks  of the volcanic  belt. A major hiatus  at the top of the SGB1  is best documented  in the northern  Presolana  area by a silcrete crust directly overlying  the Julian Annunciata Member of the Breno Formation.  In the Brembana  Valley area, the discontinuity occurs within  a greenish  siliciclastic  coastal  plain  succession, and may be traced at the top of a marker  interval of interbedded  reddish siltstones  and sandstones. The upper part (SGB2) consists  of four lithosomes. Greenish sandstones  and siltstones,  accumulating  in coastal  plains in  the south-west,  passed  northward  to mudrocks and dolostones.  In the southernmost  Camonica Valley  area,  mudrocks  are locally interbedded  with  calcarenites  containing  bored or pedogenized  lithoclasts ripped from the underlying sequence and varied  bioclasts,  restifiying to relatively  open shallow-marine conditions  during transgression. Next, thick gypsum  accumulated in coasral  salinas  barred  by locally oolitic  platform carbonates to the north. Rare sandstone lenses  occurring  in the Brembana Valley at the top of the unit conrain  exclusive rhyolitic  detritus,  indicating either  a terminal phase of explosive  volcanism  or erosion of older  felsic volcanic products.
Keywords: Semi-arid Fan; Coastal Plain; Sabkha/Lagoon; Salina; Carbonate Platform; Sandstone Petrography; Climate; Late Carnian; Southern Alps